Blended of Learning Styles through creative and critical thinking - Asbar Asbar; Kasdir Kasdir; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2020)
Learning style through creative and critical thinking is one of the soft skill attributes expected of learning style in science education. The learning style of the concept of learning style is formed from birth. Some concepts are formed at pre-school age as prejudice. Simple experiments implemented into games and games have an important role in the formation of science concepts. This study presents the results of research into the development of educational methods that are appropriate to the age development of children. Design-based research that has been used. Student learning styles in terms of the learning environment show that the majority prefers to study in a quiet environment; bright rooms; with cold temperatures; sit on a chair or soft pillow. Despite the fact that in terms of psychological preferences, the majority are investigative to learn sequentially and reflectively.